2020
DOI: 10.3390/jcm9030653
|View full text |Cite
|
Sign up to set email alerts
|

Does Previous Pelvic Organ Prolapse Surgery Influence the Effectiveness of the Sub-Urethral Sling Procedure

Abstract: Pelvic organ prolapse (POP) often co-occurs with stress urinary incontinence. There is no consensus on whether prolapse repair and anti-incontinence surgery should be performed concomitantly or separately, in a two-step manner. The present study evaluated the effects of the tension-free vaginal tape (TVT) procedure in patients who had previously undergone pelvic floor repair (study group), compared to women who underwent TVT insertion only (control group). The study group comprised 84 patients who underwent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Two-step or sequential treatment has been proposed as an alternative to avoid overtreatment and surgical complications. 9 We found that undergoing concomitant rMUS and RSC treatment was associated with a nearly 4-fold increased failure rate for SUI compared with rMUS alone for women without prolapse. We are not able to comment on the effects of POP stage in this study because its reporting was an inherent difference between groups and selection criteria for procedures performed.…”
Section: Discussionmentioning
confidence: 74%
“…Two-step or sequential treatment has been proposed as an alternative to avoid overtreatment and surgical complications. 9 We found that undergoing concomitant rMUS and RSC treatment was associated with a nearly 4-fold increased failure rate for SUI compared with rMUS alone for women without prolapse. We are not able to comment on the effects of POP stage in this study because its reporting was an inherent difference between groups and selection criteria for procedures performed.…”
Section: Discussionmentioning
confidence: 74%
“…During follow‐up, 5.5% of the patients required a subsequent anti‐incontinence procedure. It has been demonstrated that a two‐step approach to POP and urinary incontinence is as safe and effective as primary sling placement 28 . In fact, according to the theory of integral system by Petros et al., bladder reposition and reinforcement of cardinal and uterosacral ligaments may also correct further urinary symptoms, such as urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that a two-step approach to POP and urinary incontinence is as safe and effective as primary sling placement. 28 In fact, according to the theory of integral system by Petros et al, bladder reposition and reinforcement of cardinal and uterosacral ligaments may also correct further urinary symptoms, such as urinary incontinence. In this cohort, only 30.8% of the patients who complained of preoperative SUI continued to report symptoms in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed approach however may lead to under-treatment. If bothersome SUI happens postoperatively, a subsequent anti-incontinence procedure will be performed, although it is demonstrated as safe and effective as primary TVT implantation, it will increase the costs and the risks arising from a new surgery 26 . The universal approach may reduce the incidence of postoperative SUI in both symptomatic and asymptomatic POP patients 27,28 .…”
Section: Sui Often Coexists With Popmentioning
confidence: 99%